D2 statistic technique used for analysis of genetic divergence among Gir crossbreds - Mote, Mahendra Gorakh; Narwade, Vishnu Eknath; Gaikwad, Ulhas Shivaji; Sakhare, Pramodkumar Shriram (Indian Journal of Dairy Science, 2020)
D2 analysis is used for selection of genetically divergent parents. The concept of D2 was originally developed by P. C. Mahalanobis in 1928. It is used to measure degree of diversification and determines relative portion of each component trait to total divergence. The study aimed to estimate the genetic divergence among FG (50% HF+50% Gir), IFG (FG Interse), FJG (50% HF+25% Jersey+25% Gir), IFJG (FJG Interse) and R (50% HF+12.50% Jersey+37.50% Gir) crosses of Gir on the basis of age at first calving, first calving interval, lactation milk yield, lactation length and lactation milk yield per day of calving interval using Mahalanobis D2 statistics. The genetic group differences were significant (P<0.01) for all traits separately and simultaneously (V test) based on five traits. The differences in the D2 values among all the genetic groups combinations, were significant except IFG with R genetic group combination. The total D2 values for AFC, 1st CI, LMY, LL and LMY/CI were 20.53, 0.71, 4.37, 4.16 and 0.26 respectively. The contribution of AFC to the total D2 value was maximum as 68.37 per cent and lowest of LMY/CI as 0.87 per cent. Among the clusters formed on the basis of D2 values, IFG, IFJG and R formed one cluster, whereas, FG and FJG formed second cluster. The magnitude of inter-cluster distance was greater than intra-cluster distance.